2015
DOI: 10.1002/art.39243
|View full text |Cite
|
Sign up to set email alerts
|

Articular Cartilage Endurance and Resistance to Osteoarthritic Changes Require Transcription Factor Erg

Abstract: Objective To determine whether and how transcription factor Erg participates in the genesis, establishment and maintenance of articular cartilage. Methods Floxed Erg mice were mated with Gdf5-Cre mice to create conditional mutants lacking Erg in their joints. Mutant and control joints were subjected to morphological and molecular characterization and also experimental osteoarthritis (OA) surgery. Gene expression, promoter reporter assays and gain- and loss-of-function in vitro tests were used to characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 52 publications
0
28
0
Order By: Relevance
“…Our EMSA analyses implicated the Ets family of transcription factors as positive regulators of expression. Members of this family have previously been reported to have a role in OA via regulation of the expression of chondrogenic genes . Detailed analysis of these Ets transcription factors in the context of the ALDH1A2 association signal and ALDH1A2 expression is now warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Our EMSA analyses implicated the Ets family of transcription factors as positive regulators of expression. Members of this family have previously been reported to have a role in OA via regulation of the expression of chondrogenic genes . Detailed analysis of these Ets transcription factors in the context of the ALDH1A2 association signal and ALDH1A2 expression is now warranted.…”
Section: Discussionmentioning
confidence: 99%
“…ERG is strongly expressed in PCs and JPs [132]. Its inactivation in JPs ( Gdf5Cre ) does not affect joint formation [133], but its transgenic overexpression ( Col2a1 ) prevents GPC maturation and induces expression of the ACC marker tenascin-C. Interestingly, mice inactivating ERG in JPs develop osteoarthritis as they age and are more sensitive to surgically induced osteoarthritis than wild-type mice. Molecular studies have suggested that the genes for PTHrP and lubricin (encoded by Prg4 , a superficial ACC marker) might be part of the ERG targetome.…”
Section: Helix-turn-helix Transcription Factorsmentioning
confidence: 99%
“…Cux1 and the C‐1‐1 isoform of the Ets factor Erg are both expressed at developing murine joints and can repress cartilage differentiation upon misexpression. Loss of Erg in Gdf5 + joint precursors did not, however, alter joint specification in mice, although it did lead to increased susceptibility to age‐ and injury‐induced osteoarthritis of the knee . Recent work in zebrafish has found roles for the Iroquois family of transcriptional repressors in joint specification.…”
Section: Controlling Chondrocyte Identity At the Jointmentioning
confidence: 99%